Indigenising the curriculum: Transcending Australian geography's dark past. (12th September 2021) - Williams, Stewart; Anders, Robert; Vreugdenhil, Roger; Byrne, Jason
Abstract: Australian geography has been implicated in the White settler colonial project, including in the dispossession of Aboriginal peoples from their lands and the denigration of Aboriginal knowledges. Recognising the harm caused by this racist past is crucial if geography education is to play a stronger role in decolonisation. Much work is already underway. This article reports on a process to Indigenise the curriculum, building a partnership between Aboriginal people and Australian geography educators at the University of Tasmania. Tasmanian geographers and spatial scientists have begun working with Aboriginal people to come to terms with the discipline's history of genocide, dispossession and cultural politics of extinction. A workshop that was the foundation for this process generated valuable insights into how to include the knowledge and practices of Aboriginal peoples in geography and planning curricula; build communities of practice; and learn to live lawfully and lore‐fully on Country. Lessons learned have informed curriculum renewal and are helping to build new relationships. Abstract : Navigating pathways and processes for decolonising and Indigenising curricula can be challenging in the face of past and continuing injustices and trauma. We report on a foundational workshop to Indigenising geography and planning courses and the three key insights generated: embedding Aboriginal knowledge and practices in units; cultivating communities of practice; and importantly, learning to live lawfully and lore‐fully on Country. Indigenising helps address injustices and, in the very process of renewal, opportunities to refresh and reinvigorate ideas, knowledges and curricula blossom.